Traficul și consumul de droguri din perspectiva respectării drepturilor omului - Claudiu Mihail Roman; Venera Bucur; Alexandra Marilena Mioc (Drepturile Omului)
With the fall of communism and the emergence of new social phenomena, drug trafficking and consumption began to become visible in Romania as well. The continuous increase in the standard of living in Romania, especially after the accession to the European Union, associated with the ignorance of some aspects regarding the consequences in terms of health and individual well-being, have caused a number of young and less young people to become frequent or occasional drug users. The statistics of the National Anti-Drug Agency are relevant in this. In addition to the classic legal aspects and health, respectively social and individual well-being, there are also aspects related to human rights violations. Drug trafficking and consumption are flagrant violations of human rights due to the consequences they cause on an individual, family and community level.